2014
DOI: 10.1111/apt.12956
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of baclofen on the functional anatomy of the oesophago-gastric junction and proximal stomach in healthy volunteers and patients with GERD assessed by magnetic resonance imaging and high-resolution manometry: a randomised controlled double-blind st

Abstract: Summary Background The mechanism of reflux protection may involve a ‘flap valve’ at the oesophago‐gastric junction (OGJ). Aim To assess the effects of baclofen, a gamma‐aminobutyric acid receptor type‐B (GABA‐B) agonist known to suppress reflux events, on the ‘functional anatomy’ of the OGJ and proximal stomach after a large test meal. Methods Twelve healthy volunteers (HVs) and 12 patients with gastro‐oesophageal reflux disease (GERD); with erosive oesophagitis or pathological oesophageal acid exposure comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
2
20
0
4
Order By: Relevance
“…[4][5][6] A nationwide French study now published reports on 36 patients with olmesartan-associated enteropathy. 7 This important study further supports the association between olmesartan and sprue-like enteropathy. Interestingly, this report also includes four patients with severe diarrhoea and normal villi, which suggests a spectrum of histological damage.…”
Section: Acknowledgementsupporting
confidence: 61%
See 1 more Smart Citation
“…[4][5][6] A nationwide French study now published reports on 36 patients with olmesartan-associated enteropathy. 7 This important study further supports the association between olmesartan and sprue-like enteropathy. Interestingly, this report also includes four patients with severe diarrhoea and normal villi, which suggests a spectrum of histological damage.…”
Section: Acknowledgementsupporting
confidence: 61%
“…4 In the current study the effects of baclofen, a medication known to suppress TLOSRs, 5,6 on OGJ structure and function was assessed in a randomised, placebo-controlled trial. 7 The primary outcome was that the insertion angle was reduced towards normal levels by baclofen in reflux patients. In addition intra-abdominal LOS pressure was increased.…”
mentioning
confidence: 99%
“…Alginates cover the acid pocket and reduce esophageal contact exposure—safety profile is excellent and these may serve a complementary role for some patients . Baclofen, a gamma amino butyric acid B receptor agonist, has been shown to reduce TLESRs and reflux episodes; however, efficacy is limited due to adverse effects and tachyphylaxis . Prokinetics increase gastric emptying and esophageal contraction and may have modest efficacy in some patients; however, limited benefit must be weighed against medical tolerability and risk .…”
Section: Management Considerationsmentioning
confidence: 99%
“…61 A further study confirmed these findings by showing reduced postprandial acid reflux events in both healthy volunteers and GERD patients by inhibiting TLESRs and increasing LES tone. 62 …”
Section: Baclofenmentioning
confidence: 99%